Increased proportions of dendritic cells and recovery of IFNγ responses in HIV/HCV co-infected patients receiving ART - Saraswati, H.; Lee, Silvia; Tan, D.; Yunihastuti, E.; Gani, R.; Price, Patricia (2015)
Dendritic cell (DC) numbers and functions can be affected by HIV and HCV disease, but the effects of antiretroviral therapy (ART) on DC and the implications of these changes are unclear. We examined circulating DC in samples from Indonesian patients beginning ART with advanced HIV disease and documented mild/moderate HCV hepatitis. Frequencies of myeloid and plasmacytoid DC increased after 6 months on ART, but frequencies of DC producing IL-12 or IFNα following stimulation with TLR agonists (CL075, CpG) did not change. IFNγ responses to CL075, HCV and other antigens rose over this period. Hence increased IFNγ responses during ART may be associated with increased DC frequencies rather than changes in their functional capacity.